Implementation of the drug samples tracing system - V. N. Kotikov; V. A. Petrosyants (Регуляторные исследования и экспертиза лекарственных средств)
The article elaborates on a general overview of the tracing system and the possibilities of its implementation in the circulation of medicines. Moreover, it presents several variants of pharmaceutical production marking and the characteristics of those. The article touches upon the challenges of drug samples tracing system information support.